Vapor-phase polymerization of pyrrole on flexible substrate at low temperature and its application in heat generation - Shang, Songmin; Yang, Xiaoming; Tao, Xiao-ming; Lam, Song Song (Polymer international, 2010)
The vapor‐phase polymerization of pyrrole to form conducting polypyrrole (PPy) films was applied to coat flexible poly(ethylene terephthalate) (PET) fabrics. A PPy‐coated PET fabric surface resistance of 200–20 000 Ω□−1 was obtained. The polymerization conditions, such as the concentration of oxidant and the reaction time and temperature, were systematically investigated. The coated fabric samples exhibited increasing temperatures when subjected to a fixed DC voltage. This result indicates the potential of these PPy‐coated fabric materials for heating applications. Copyright © 2009 Society of Chemical Industry The vapor phase polymerization of pyrrole at low temperature was applied to coat flexible polyethylene terephthalate (PET) fabrics with a high uniform polypyrrole (PPy) film. The coated fabric samples show a temperature rising when subject to a fixed DC voltage.